2013
DOI: 10.1016/j.mjafi.2013.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Proportion of Rh phenotypes in voluntary blood donors

Abstract: a b s t r a c tBackground: The Rh system is the major blood group system besides ABO system. Even after proper blood grouping and cross matching there is a possibility of alloimmunization and antibody production in the recipients against the Rh or minor blood group antigens like Results: The phenotypic frequencies of Rh blood groups in the studied population were D-92.25%, C-87.55%, E-26.55%, c-51.06% and e-98.42%. Thus 'e' was the most common and E was the least common of all the Rh types. Phenotypically DCCe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
8
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 6 publications
5
8
2
Order By: Relevance
“…B blood group was found to be most common similar to other studies from India [8]. In Rh system D antigen frequency was found to be 93.8% which was comparable to other studies from India [9][10][11]. On the basis of expression of different antigen of Rh system most common phenotype was found to be of DCe/DCe (R1R1) //DCe/Ce (Rr) (44.7%) and similar findings by Agarwal (42.93%), Thakral et al (43.8%) and Sarkar (35.2%) [8,9,11].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…B blood group was found to be most common similar to other studies from India [8]. In Rh system D antigen frequency was found to be 93.8% which was comparable to other studies from India [9][10][11]. On the basis of expression of different antigen of Rh system most common phenotype was found to be of DCe/DCe (R1R1) //DCe/Ce (Rr) (44.7%) and similar findings by Agarwal (42.93%), Thakral et al (43.8%) and Sarkar (35.2%) [8,9,11].…”
Section: Discussionsupporting
confidence: 86%
“…Incidence of anti-D is very uncommon in country with low frequency of Rh (D) antigen. In Indian population due to relatively high prevalence of D negative, D typing is a must [11]. Among Rh minor antigens those are present less commonly in predominant phenotype alloantibody would be more common against them.…”
Section: Discussionmentioning
confidence: 99%
“…In negative subjects, the most commonly seen predicted Rh phenotype in this study was ce (rr) which is similar to that reported in study by Thakral et al 6 In contrast ce/ce (rr) was the least common phenotype reported by Sarkar et al Thakral et al showed ce/cE as the rarest phenotype. 6,9 DCe/dce (R 1 r) 31.1% and Dce/dce (R 0 r) 22.9% were the most common phenotype reported in whites and blacks respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of other Rh Antigens (C, c, E, e) among the study population was compared with that of other studies carried out in India at different regions 3,[11][12][13][14] and with other populations 2,15-17 as presented in (Table 5). …”
Section: 11mentioning
confidence: 99%